Penanaman Nilai-Nilai Dakwah Dalam Proses Pembelajaran Agama Di Smp Negeri 4 Filial Kelas Jauh Usaha Jaya - Fajrin, Muhammad; Hartinah; Fatima, Siti (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2022)
In spreading Islam to all corners of the world, da'wah became one of the contributors to spreading this so that Islam became a religion that was embraced and believed in by various nations in all corners of the world. This research aims to review and explain the instillation of da'wah values ​​through the religious learning process at SMP Negeri 4 Filial, Usaha Jaya Class. The method used in this research is a qualitative research method by collecting data through observation. The results of this research show that the cultivation of da'wah values ​​is still high in SMP Negeri 4 Filial, Usaha Jaya Class. The factor causing the high value of da'wah in this area is the early planting carried out by the parents of these students.